Incorporation of new product development technologies in the traditional Pewter sector - Jorge Lino (2008)
The aggressive competition that companies,operating in different industrial sectors, arenowadays subjected is the result of manufacturingto a global market where consumers arecontinuously demanding more sophisticated newproducts with higher quality and shorter life cycles.These new challenges demand capacities tointernally develop new products using digitalmodelling, rapid prototyping, conversiontechnologies, rapid manufacturing and others toolsthat are already common in industrial sectors suchas aeronautics, transportation, medical and others.In this communication the authors present howthe adoption of these technologies werefundamental to rapidly create new products in atraditional manufacturing pewter company that stillhas an intensive human labour and traditional wayfor product development, and how these newmethodologies were fundamental to quicklyintroduce, with success, these products in theinternational market.